Our dynamic Sun: A principal source of new physics - Dwivedi B.N. (My University, 2025)
Our dynamic Sun provides a principal source of new physics. Among the many exotic objects available for study, the seemingly pedestrian Sun exhibits a variety of phenomena that defy contemporary theoretical understanding. After presenting some history, we address some unanswered questions in coronal physics (e.g. coronal heating and solar wind acceleration) with new results from SOHO. Magnetic energy release on the Sun (explosive events) and coronal mass ejection (key to understanding space weather) are also briefly presented. We conclude with the present scenario and the exciting promise that SOHO holds in the unravelling of some of the known mysteries of our own Sun and in presenting us with some new ones.